Decreased Serum Brain-Derived Neurotrophic Factor in Poststroke Depression: A Systematic Review and Meta-Analysis - Chunhui Zhang (Frontiers in Psychiatry, 2022)
BackgroundsThere were conflicting results on the comparison of brain-derived neurotrophic factor (BDNF) levels between poststroke depression (PSD) patients and stroke patients without PSD among previous studies. Thus, we conducted this systemic review and meta-analysis to explore the alteration of serum BDNF levels in PSD.MethodsThis study included articles from the Web of Science and PubMed databases that were published before December 2021. STATA 12.0 software was used to compute the standardized mean difference (SMD) and 95% confidence interval (CI) regarding the comparison of serum BDNF in PSD and stroke patients without PSD.ResultsWe collected the mean value and standard deviation (SD) of serum BDNF in PSD and stroke patients without PSD from six studies (PSD: n = 268, stroke patients without PSD: n = 425). The present meta-analysis showed decreased serum BDNF level in patients with PSD, compared to stroke patients without PSD with a random-effects model (mean value of BDNF level [PSD vs. stroke patients without PSD]: 14.106 vs. 17.995 ng/ml; SMD = –1.578; 95% CI: –2.820, –0.337; I2 = 97.8%, p-value for Q test < 0.001).ConclusionBrain-derived neurotrophic factor may work as a potential biomarker to predict the risk of PSD among stroke survivors. More large-sample clinical trials exploring the alteration of serum BDNF levels in PSD among stroke patients need to be conducted to verify this result.